Circular Business Models in Agriculture: A Bibliometric Assessment of Implementation and Economic Sustainability - Judijanto, Loso; Mardianto, Dedi; Hertini , Etty Sri; Suryaningrum , Dyah Ayu (West Science Social and Humanities Studies, 2025)
This study employs a bibliometric analysis to assess the implementation and economic sustainability of circular business models (CBMs) in agriculture. Using data exclusively from the Scopus database, the research analyzes citation trends, key publications, and thematic clusters through VOSviewer. The findings reveal that sustainability and agriculture are central themes, with strong interconnections to economic growth, environmental economics, and technological advancements. The study identifies three major research clusters: sustainability and business models, agriculture and environmental concerns, and food security and supply chain management. Additionally, temporal analysis indicates a shift from environmental sustainability towards integrated economic and technological solutions. While the co-authorship and country collaboration networks highlight expanding international research efforts, fragmentation persists, suggesting a need for stronger interdisciplinary cooperation. The study underscores the importance of circular economy approaches and innovation in fostering sustainable agricultural practices. These insights provide valuable guidance for policymakers, researchers, and practitioners in advancing the transition towards sustainable and economically viable agricultural systems.